THE EFFECT OF CONTACT TIME AND BIOSORBENT TEMPERATURE ON THE ADSORPTION OF INDIGO CARMINE DYES IN KAPOK HUSK BIOSORBENT MODIFIED WITH SNAIL MEAT AND KINETIC STUDY - Rahmiana Zein; -, Raisha Mashelina (ALOTROP, 2023)
The use of indigo carmine dye in the textile industry is a source of pollution for the environment. The presence of dye pollutants in the environment can threaten the health of living creatures and the sustainability of the ecosystem. This research uses kapok husk biosorbent modified with snail meat. Previously, research on adsorption was carried out on metals and cationic dyes from kapok husk, then in this research adsorption was carried out using the batch method to adsorb anionic dyes. The biosorbent modification process using snail meat aims to add active sites in the form of functional groups to the biosorbent to optimize the dye adsorption capacity. The contact objective of this research is to determine the heating time and temperature conditions for optimal adsorption of indigo carmine using the batch method. The research results showed that the adsorption capacity was at optimum conditions for the adsorption of indigo carmine at a contact time of 60 minutes and a temperature of 25°C.